Metabolic profiling and gene expression analyses provide insights into cold adaptation of an Antarctic moss Pohlia nutans - Liu, Shenghao; Li, Tingting; Fang, Shuo; Zhang, Pengying; Yi, Dan; Cong, Bailin; Zhang, Zhaohui; Zhao, Linlin (Frontiers in Plant Science, 2022)
Antarctica is the coldest, driest, and most windy continent on earth. The major terrestrial vegetation consists of cryptogams (mosses and lichens) and two vascular plant species. However, the molecular mechanism of cold tolerance and relevant regulatory networks were largely unknown in these Antarctic plants. Here, we investigated the global alterations in metabolites and regulatory pathways of an Antarctic moss (Pohlia nutans) under cold stress using an integrated multi-omics approach. We found that proline content and several antioxidant enzyme activities were significantly increased in P. nutans under cold stress, but the contents of chlorophyll and total flavonoids were markedly decreased. A total of 559 metabolites were detected using ultra high-performance liquid chromatography/electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS). We observed 39 and 71 differentially changed metabolites (DCMs) after 24 h and 60 h cold stress, indicating that several major pathways were differentially activated for producing fatty acids, alkaloids, flavonoids, terpenoids, and phenolic acids. In addition, the quantitative transcriptome sequencing was conducted to uncover the global transcriptional profiles of P. nutans under cold stress. The representative differentially expressed genes (DEGs) were identified and summarized to the function including Ca2+ signaling, ABA signaling, jasmonate signaling, fatty acids biosynthesis, flavonoid biosynthesis, and other biological processes. The integrated dataset analyses of metabolome and transcriptome revealed that jasmonate signaling, auxin signaling, very-long-chain fatty acids and flavonoid biosynthesis pathways might contribute to P. nutans acclimating to cold stress. Overall, these observations provide insight into Antarctic moss adaptations to polar habitats and the impact of global climate change on Antarctic plants.